Bioactive Compounds from Kalanchoe Genus Potentially Useful for the Development of New Drugs - Luana Beatriz dos Santos Nascimento; Livia Marques Casanova; Sônia Soares Costa (Life, 2023)
The genus Kalanchoe Adans. (Crassulaceae) is native to Madagascar and comprises 145 species, being naturalized in the tropics and cultivated worldwide. In addition to having ornamental value, several Kalanchoe species are commonly used in popular medicine for the treatment of inflammatory conditions, wounds, gastric ulcers, and other diseases. The great importance of the genus is reflected on its acknowledgment by traditional and alternative health systems and organizations, as well as on the growing number of papers reporting pharmacological properties of extracts and isolated compounds from Kalanchoe. Among these properties, we highlight anti-inflammatory, antitumor, wound healing, antiulcer, and muscle relaxing properties. These activities are attributed mostly to flavonoids and bufadienolides, the main secondary metabolites reported in Kalanchoe extracts. While bufadienolides are generally related to cytotoxic and muscle relaxing activities, flavonoids are commonly reported as anti-inflammatory and wound healing agents. This review provides up to date information and perspectives on bioactive compounds from the Kalanchoe genus that are potentially useful for the development of new drugs. It includes not only a discussion on the advantages of the Kalanchoe species as source of bioactive compounds, but also the gaps, opportunities, and challenges to translate the acquired knowledge into innovation for drug development.